Chromosome-Level Genome Assembly of Cyrtotrachelus buqueti and Mining of Its Specific Genes - Fu, Chun; Long, WenCong; Luo, ChaoBing; Nong, Xiong; Xiao, XiMeng; Liao, Hong; Li, YuanQiu; Chen, Ying; Yu, JiaXin; Cheng, SiXuan; Baloch, Saira; Yang, YaoJun (Frontiers in Ecology and Evolution, 2021)
Background: The most severe insect damage to bamboo shoots is the bamboo-snout beetle (Cyrtotrachelus buqueti). Bamboo is a perennial plant that has significant economic value. C. buqueti also plays a vital role in the degradation of bamboo lignocellulose and causing damage. The genome sequencing and functional gene annotation of C. buqueti are of great significance to reveal the molecular mechanism of its efficient degradation of bamboo fiber and the development of the bamboo industry. Results: The size of C. buqueti genome was close to 600.92 Mb by building a one paired-end (PE) library and k-mer analysis. Then, we developed nine 20-kb SMRTbell libraries for genome sequencing and got a total of 51.12 Gb of the original PacBio sequel reads. Furthermore, after filtering with a coverage depth of 85.06×, clean reads with 48.71 Gb were obtained. The final size of C. buqueti genome is 633.85 Mb after being assembled and measured, and the contig N50 of C. buqueti genome is 27.93 Mb. The value of contig N50 shows that the assembly quality of C. buqueti genome exceeds that of most published insect genomes. The size of the gene sequence located on chromosomes reaches 630.86 Mb, accounting for 99.53% of the genome sequence. A 1,063 conserved genes were collected at this assembled genome, comprising 99.72% of the overall genes with 1,066 using the Benchmark Uniform Single-Copy Orthology (BUSCO). Moreover, 63.78% of the C. buqueti genome is repetitive, and 57.15% is redundant with long-term elements. A 12,569 protein-coding genes distributed on 12 chromosomes were acquired after function annotation, of which 96.18% were functional genes. The comparative genomic analysis results revealed that C. buqueti was similar to D. ponderosae. Moreover, the comparative analysis of specific genes in C. buqueti genome showed that it had 244 unique lignocellulose degradation genes and 240 genes related to energy production and conversion. At the same time, 73 P450 genes and 30 GST genes were identified, respectively, in the C. buqueti genome. Conclusion: The high-quality C. buqueti genome has been obtained in the present study. The assembly level of this insect’s genome is higher than that of other most reported insects’ genomes. The phylogenetic analysis of P450 and GST gene family showed that C. buqueti had a vital detoxification function to plant chemical components.